Lennon v. McCartney - Kroetch, Kimberly (My University, 2020)
In this analysis, the chord progressions used in songs by the Beatles are modelled as Markov chains to identify potential differences between songs for which John Lennon had more influence and those for which Paul McCartney had more influence. A preliminary comparison of random samples of songs from each artist did not identify noteworthy differences between Lennon and McCartney; most pieces resulted in regular Markov chains. This analysis then focusses on two songs from the Beatles – “Norwegian Wood”, primarily written by John Lennon, and “Good Day Sunshine”, primarily written by Paul McCartney – which deviated from this pattern. Similar patterns were found between the two songs despite major differences in the chords that made up each state space. In general, however, McCartney’s song had more variety in terms of the number of chords used and the paths taken between tonic chords.
Keywords: Markov chains; chord progressions; Beatles